Women in governance for development at grassroots - Palanithurai, G. (2004)
Creation of an exclusive space for women at the grassroots has augured well for the decentralised governance and administration in the country. Many thought that it was a political space for women, which they should treat as governance space. However, these leaders have perceived this space as development space and most of their governance endeavours address development issues. This article, based on the performance of elected women representatives of local bodies in Tamil Nadu, shows how in spite of their inexperience these leaders have come to grips with their new assigned role in a patriarchial society. Their perception of this new role has made much of the difference in their approach towards social, development and governance related issues. Their transparent working, concefrn towards the society and ability to lead from front display all the necessary qualities that are attributed to modern concepts of good governance. - Reproduced.
Keywords: Good governance; Women in politics